Core–shell ZnO@C:N hybrids derived from MOFs as long-cycling anodes for lithium ion batteries. Issue 13 (21st January 2020) - Guo, Yichuan; Wang, Zhaoying; Lu, Xinsheng; Lu, Jianguo; Rabia, Khatoon; Chen, Hongwen; Hu, Rui; Tang, Haichao; Zhang, Qinghua; Li, Zhoupeng
Abstract : ZnO@C:N hybrids are obtained that have a reversible capacity of 608 mA h g −1 after 500 cycles. Abstract : A core–shell hybrid of ZnO and nitrogen-doped carbon (ZnO@C:N) is designed as a long-cycling anode for LIBs. The ZnO@C:N hybrid has a high initial capacity of 1116 mA h g −1 and a reversible capacity of 608 mA h g −1 after 500 cycles at 0.1 A g −1 . The unique core–shell structure, high conductivity due to nitrogen doping, and uniform solid electrolyte interphase (SEI) film formed in the electrode are revealed to result in the remarkable electrochemical performances of the ZnO@C:N electrodes.